Chế tạo và tính chất của vật liệu nanocompozit trên cơ sở blend của cao su etylen-propylen-dien đồng trùng hợp với polyetylen tỷ trọng thấp và nanosilica - Hòa, Hoàng Thị; Hải, Lưu Như; Hùng, Lưu Đức; Kháng, Đỗ Quang (Vietnam Journal of Chemistry, 2016)
In this work, rubber blend based on ethylene-propylene-dien-terpolymer (EPDM) and low density polyethylene (LDPE) and its nanocomposite with nanosilica were prepared by melt mixing method using an internal mixer at 120 oC. The results reveal that at the EPDM/LDPE ratio 80/20 the two components are good compatible. The optimal nanosilica content for reinforcement of EPDM/LDPE blend was 25 %. By surface modification of nanosilica with bis(3-triethoxysilypropyl) tetrasulfide (TESPT) or direct mixing with TESPT, nanosilica was well dispersed in EPDM/LDPE matrix with the diameter of nanosilica below 100 nm. The mechanical properties of the nanocomposites were significantly increased, especially the elongation at break about 50 % compared to rubber blend without reinforcement. Keywords. EPDM, LDPE, blend, nanocomposite, nanosilica.